Costeffective formulation of bio-fertilizer using agricultural residues as carriers and determination of shelflife of bio-fertilizer inoculants - Akter, Taslima; Shah, SM Tanjil; Mamun, Md Arafat Al; Bari, Md Latiful; Begum, Shamima; Rahman, Naziza; Miah, Md Ibrahim (Dhaka University Journal of Biological Sciences, 2023)
Traditionally, inorganic chemical-based fertilizers is used for soil management strategies, which can cause public health and environmental threats. Alternatively, bio-fertilizer can be used to increase the productivity and sustainability of soil without causing environmental pollution. The present study aimed to cost-effectively produce bio-fertilizer using agricultural residues and determine the shelflife and efficacy of the bioinoculants. We used sterilized rice husk ash and alluvial soil (1:2) to prepare cost-effective carriers. Rhizobium sp., Azotobacter sp., and Trichoderma sp. were grown in a newly designed culture medium for economic production as bio-inoculants. The efficacy of the formulated bio-fertilizer was tested on a small scale, where it significantly improved the growth of the sponge gourd (Luffa aegyptiaca) plant (p<0.01). The formulated bio-fertilizers were stored at room temperature for one year. Initially, the total viable count of microorganisms was 8.0×107 CFU/g in the formulated bio-fertilizer. The total viable count of the bio-inoculants increased significantly after one month (2.2×108 CFU/g) and one year (2.2×109 CFU/g). Rice husk ash might have supported the growth and survival of the bioinoculants under room temperature (25°C) because of its nutrient retention capacity, adsorptive capability, and high content of silica. Therefore, this study suggests that sterile rice husk ash combined with alluvial soil can be used as a carrier for bio-fertilizers formulation with Rhizobium sp., Azotobacter sp., and Trichoderma sp. bioinoculants. Dhaka Univ. J. Biol. Sci. 32(2): 189-199, 2023 (July)